Nonwood-based composites - Abd Halip, Juliana; M. T., Paridah; Zaidon, A.; Abdul Khalil, H. P. S. (Springer, 2015)
Nonwood fibers are derived mostly from fastgrowing plants. For the past few decades, nonwood plant fibers have received much attention, especially for composite material applications, because of their low cost, low density, high specific strength, good mechanical properties, nonabrasiveness, eco-friendliness, and biodegradability. This article reviews the performance of nonwood fibers found mostly in Asia, as well as issues regarding their bonding. Because various classifications of nonwood exist, this article sorts nonwood fibers based on previous classifications with some modifications, accounting for the availability of these fibers in Asia. The mechanical and physical properties of nonwood-based composites such as fiberboard, particleboard, and veneer-based laminated products also are reviewed and discussed. All fibers demonstrate certain advantages over conventional composites, with some having better mechanical and physical properties. This article also highlights the issues and challenges regarding the use of nonwood fibers as composite materials.